'We Have no Such Custom': A Rhetorical Analysis of 1 Corinthians 11,2-16 - Smit, Joop (Ephemerides theologicae Lovanienses, 2021)
Although the question of the head covering in 1 Cor 11,2-16 has been widely studied during the last decades, scarce attention has been paid to the rhetoric of the passage. The current article intends to fill this gap by re-examining the passage according to the rhetorical categories of genus, inventio, dispositio, and elocutio. Following the rules of rhetoric, Paul urges the women in Corinth to wear a veil during prayer. He deduces this decision from Genesis 1-4, which implies that men have priority in the prayer service, but that men and women are equal outside this context.